PERANCANGAN SISTEM AKUISISI DATA PEMAKAIAN LISTRIK 1 PHASA DAYA 1300 VA PADA RUMAH TINGGAL MENGGUNAKAN DATA LOGGER - Jumiyatun, Jumiyatun; Ely, Muhammad Nasir; Sollu, Tan Suryani; Mansur, Khairunnisa; Fatmawati, Andi; Firmansyah, Rifqi (Foristek, 2025)
Electrical energy is one of the basic needs for humans today, almost every activity we do is inseparable from the use of electrical energy, the use of electrical energy must be paid according to the amount and duration of electricity use in electricity management authorized by state-owned companies, namely PT. PLN Persero using kWh meter. In the postpaid type kWh Meter (Kilo Watt Hours), we cannot know the amount of electrical power that has been used in real-time.This research aims to design a system that can acquire power consumption in kWh andpower consumption costs (Watts) real-time by utilizing the ACS712 current sensor and voltage sensor circuit as input current and voltageand then processed by Arduino Uno for processing. The data is in an application interface, then the usage data is stored automatically in the data base local by the MySQL application.The results of this study are by comparing the calculation of power consumption (Watt) and the nominal cost of electricity in anapplication interface. After the data is obtained, it can be concluded that the readings from input the current and voltage sensor in this system are not accurate and unstable, so that the comparison of the value by the kWh meter is 4.8 kWh with a nominal cost of Rp. 7,745.76, while in this system design the power value obtained is 9.08 kWh with a nominal usage fee of Rp. 14,652.39. Then the difference in value between the calculation of kWh and the design of this system is 4.28 kWh, with a nominal difference in the cost of using it of Rp. 6,906.63.